2020
DOI: 10.1051/mfreview/2020027
|View full text |Cite
|
Sign up to set email alerts
|

Multi-optimization of process parameters for machining of a non-conductive SiC ceramic composite by non-conventional machining method

Abstract: The objective of the study is to predict the optimized set of the input parameters for the machining of non-conductive silicon carbide (SiC) by electric discharge machining (EDM). The insulated SiC ceramic composite machining was performed with 4 volumes (by percentage) of carbon nano (CNT) the SiC, which makes it electrically conductive. SiC has very good mechanical properties due to its widespread application in the aerospace, MEMS, and bio-sensor industries. This application requires a highly precise machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Using the equations [9][10][11][12][13][14], relative weight, utility degree and its rank were calculated. The results are shown in Table 6.…”
Section: Copras Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the equations [9][10][11][12][13][14], relative weight, utility degree and its rank were calculated. The results are shown in Table 6.…”
Section: Copras Methodsmentioning
confidence: 99%
“…The machining parameters were optimized in Electrical Discharge Machining (EDM) operation using MOORA technique and observed the optimum outputs such as material removal rate (MRR), plasma flushing efficiency (PFE), surface-roughness (SR) and recast layer thickness were achieved by intermingling MOORA with Weighted Principal Component Analysis (WPCA) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some feasible NCM procedure satisfying the requirement of users was initially generated and those procedures were ranked with respect to their suitability to meet the required machining standards and operations. P. Chaudhury and S. Samantaray in [2] developed professional systems for choosing the best NCM procedure under constrained machining and material conditions. It would depend on the priority figures of various criteria and sub-criteria for particular NCM procedure 'choice' issue, and NCM procedure with higher acceptability index was finally recognized.…”
Section: Introductionmentioning
confidence: 99%
“…As a conclusion, he demonstrated that the model established by DiBitonto et al [1] has the strongest agreement with experimental data. Recently published papers (Shuvra Das et al [3]; Kansal et al [17]; Marafona and Chousal [18]; Ghanem et al [19]; Salah, N.B et al [20,21]; Bhondwe et al [22];…”
Section: Introductionmentioning
confidence: 99%
“…Shuvra Das et al [3], Ghanem et al [19], and Salah et al [20,21] recommended an 18% value, while Vinod Yadav et al [23] recommended an 8% value. Marafona and Chousal [18] assume that the fraction of energy transmitted to the workpiece is 50%. According to Kansal et al [17] and Bhondwe et al [22], the powder fraction (Fc) is dependent on the dielectric fluid used.…”
Section: Introductionmentioning
confidence: 99%